Continuity and innovation in the Aramaic legal tradition - Gross, Andrew D. (Leiden ; Boston : Brill, 2008)
This book argues that Aramaic scribes from antiquity drew upon a common legal tradition. It identifies the distinctive elements that form the core of this tradition and traces their antecedents within the cuneiform record.
Introduction --The acknowledgment of receipt clause -- The investiture clause -- The warranty clause -- Conclusion.
Includes bibliographical references (pages 204-226) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 650
Keywords: Law -- Middle East -- History -- Sources; Law -- Egypt -- Elephantine -- History -- Sources; Manuscripts, Aramaic (Papyri) -- Egypt -- Elephantine; Law, Ancient -- Sources; Jewish law -- Sources; LAW -- Administrative Law & Regulatory Practice; Jewish law; Law; Law, Ancient; Manuscripts, Aramaic (Papyri); Egypt -- Elephantine; Middle East; Rechtsquelle; Keilschrift; Alter Orient; Aramäisch.; Electronic books; Electronic books -- History -- Sources; History; Sources; Electronic book; Electronic books